Retrospective Analysis of the Prevalence and Risk Factors of Retinopathy of Prematurity in a Single-Center Cohort in Romania and Comparison with National and European Data - Zsuzsánna Simon-Szabó; Sándor Pál; Aliz Pándi; Zsuzsanna Gáll; Hajnal Finta; Zsuzsánna Incze-Bartha; Cristina Maki; Manuela Cucerea (Medicina)
Background and Objectives: This study investigated and compared with European literature data the incidence, severity, and perinatal risk factors of retinopathy of prematurity (ROP) in preterm infants admitted to the Premature Department of Mureş County Clinical Hospital over a two-year period (January 2022–December 2023). Materials and Methods: ROP screening was performed in 96 infants (76.8%) according to professional guidelines. A literature review was conducted to compare our findings with national and European data. Significant differences were identified in comparisons with studies from Cluj-Napoca (p = 0.0125), Timișoara, and Bucharest (p < 0.0074), as well as Serbia and Croatia when stratified by gestational age limits. The variations in GA thresholds (32 vs. 34 weeks) between studies required stratified analyses to ensure meaningful comparisons. The included European studies provided data on screening criteria, prevalence, and associated risk factors, offering a comprehensive perspective on screening effectiveness. Results: Among the 149 admitted patients, 125 were preterm (n = 125). Of the screened patients, 20 (20.83%) infants were diagnosed with ROP, including 13 boys (65%) and 7 girls (35%), all requiring prolonged respiratory support, and 55% of them needed blood transfusion. The average birth weight of affected infants was 1030.5 g (550–1700 g ), and the mean gestational age was 28.3 weeks (25–34 weeks). In those found to have stage 2 and 3 ROP in zone II with plus disease (n = 6), intravitreal anti-VEGF injections and/or retinal laser treatments were performed. Notably, no cases of ROP-related blindness were recorded. Conclusions: To our knowledge, this is the first study to compare ROP prevalence and screening outcomes across Romanian national centers. Identified risk factors in this cohort, such as respiratory distress syndrome, oxygen therapy, blood transfusion, and intraventricular hemorrhage, are consistent with the existing literature data. These findings underscore the importance of standardized screening criteria and effective management protocols to prevent ROP-related blindness. The comparative approach of this study highlights the necessity of harmonized internationally applied criteria to facilitate robust comparisons and, more importantly, improve patient care outcomes.